Precise H2 supply enables quantitative control of on-demand deep nitrate removal while preserving denitrification completeness - Ge Yan; Zhen-Xiang Jiang; Jia-Le Wu; Ting Wang; Jun-Tong Hu; Li-Wen Qiu; Chen Zhou; Hongqiang Ren (Water Research, 2026)

Novel D-A1-A2-π-A self-assembled monolayer in suppressing the Voc deficit of the wide-bandgap perovskite solar cells - Dong-Tai Wu; Yu Hsuan Lin; Yi-Chen Lin; Hsin Li; Yu-Chen Liang; Yu-Tong Hung; Yi-Sheng Lin; Wei-Jia Qiu; Shi-Chun Liu; Yuan Jay Chang; Chieh-Ting Lin (Chemical Engineering Journal, 2026)

Thiocyanate-driven denitrification with mixotrophic flexibility for real coking wastewater treatment: Novel insights into nitrogen cycling - Yu Zhang; Yu-Tong Li; Quan Zhang; Xue-Ting Wang; Wei Wang; Aijie Wang; Jun Ma; Duu-Jong Lee; Nanqi Ren; Chuan Chen (Water Research, 2026)

Integrated network pharmacology and experimental validation to elucidate the mechanism of WIN55,212–2 in mitigating sepsis-induced pulmonary fibrosis in mice - Quan He; Dei-xing Yang; Lin Duo; Tong-ling Shi; Yuan-wei Yang; Jie-cheng Li; Shu-ting Li; Shang-shang Zhu (Tissue and Cell, 2026)

Trade-off between structural resilience and kinetics induced by N2-plasma activated CN− vacancies in high-entropy Prussian blue cathodes for sodium-ion storage - Qiang Liu; Yan-Jiang Liu; Miao-Yu Li; Ting-Liang Xie; Hao-Tian Tong; Bo Jin; Shuang-Feng Yin (Chemical Engineering Journal, 2026)

Spatiotemporal scaling of gully erosion susceptibility: Integrating seasonal dynamics across regional and watershed contexts - Yanyan Xu; Yanru Wen; Seyed Hamidreza Sadeghi; Tong Zhou; Jing Yang; Ting-yong Li; Bingxue Zhu; Wenbin Wu (CATENA, 2026)

Influence of cutterhead cooling water on microwave-induced fracturing of hard rocks during microwave-TBM synchronous operation - Tianyang Tong; Xia-Ting Feng; Chengxiang Yang; Feng Lin; Shiping Li; Xiangxin Su (Tunnelling and Underground Space Technology, 2026)

The Anti-Fibrotic Effects of Irisolidone via Peroxisome Proliferator-Activated Receptor Gamma - Zi-an Pan; Li-ting Tong; Zhe-min Wang (Tissue and Cell, 2026)

Prevalence and risk factors of bovine tuberculosis in dairy cattle, 2020–2025: A systematic review and meta-analysis of available literature - Qi Wang; Xiao-Nan Wang; Xiao-Qun Liu; Long-Ge Zhao; Zi-Tong Jing; Tian Tian; Jia-Ting Zhang; Yi-Xing Zhao; Jian-Ming Li; Nai-Chao Diao; Kun Shi; Rui Du (Preventive Veterinary Medicine, 2026)

Systematic cadmium isotope fractionation between the organic and mineral fractions of soils - Jiawen Zhou; Tingting Mu; Ting Gao; Rebekah E.T. Moore; Mark Rehkämper; Yufang Sun; Zhen Zeng; Xinyang Li; Shijin Guo; Tong Zhou; Longhua Wu; Yongming Luo (Journal of Hazardous Materials, 2026)

Erratum to “Sulfur disproportionation in engineered environmental systems: A critical review of mechanisms, applications, and emerging perspectives” [Water Research, Volume 300, 1 August 2026, 125856] - Yu Zhang; Yu-Tong Li; Quan Zhang; Wei Wang; Xue-Ting Wang; Lei Zhao; Ai-jie Wang; Jun Ma; Duu-Jong Lee; Nan-qi Ren; Chuan Chen (Water Research, 2026)

Sulfur disproportionation in engineered environmental systems: A critical review of mechanisms, applications, and emerging perspectives - Yu Zhang; Yu-Tong Li; Quan Zhang; Wei Wang; Xue-Ting Wang; Lei Zhao; Ai-jie Wang; Jun Ma; Duu-Jong Lee; Nan-qi Ren; Chuan Chen (Water Research, 2026)

Rockburst mitigation by microwave destressing in a deep drill-and-blast tunnel: thermal–damage–stress evolution with a slotted-wall coaxial applicator - Yuntan Ao; Xia-Ting Feng; Shiping Li; Xiaojun Zhang; Juan He; Tianyang Tong; Yifan Zhang; Feng Lin (Tunnelling and Underground Space Technology, 2026)

Changes in flavor profiles and microbial community diversity throughout rice wine fermentation with Rhizopus oryzae from different sources - Ting Tong; Jing-Rong Hu; Zhen-Jia Li; Zi-Zhen Qin; Cai-Hua Shi; Han-Cheng Wang (International Journal of Food Microbiology, 2026)

Impact of Atractylodes lancea Ultrafine Powder on Crucian Carp (Carassius auratus) Growth, Body Composition and Hypoxia Tolerance - Ting Zhang; Jianying Pu; Yutong Yuan; Min Liu; Tong Xu; Xingyu Shi; Gangfu Chen; Jing Xu; Qihui Yang; Huatao Li (Fishes, 2026)
The goal of this study is to assess how dietary Atractylodes lancea ultrafine powder (AUP) affects crucian carp (Carassius auratus) growth, body composition, and hypoxia tolerance. A total of 630 crucian carp (13.21 ± 0.17 g) were fed diets containing 0.0%, 3.0%, 6.0%, 9.0%, 12.0%, 15.0%, and 18.0% AUP for 15 days. In crucian carp, dietary AUP was observed to improve protein content and decrease weight gain and fat content (p

Lactiplantibacillus Plantarum O126 Postbiotics Boost growth, Antioxidant levels, Disease resistance, and Gut Health in Sea Cucumber (Apostichopus japonicus) - Feng-Li Chen; Hui-Ting Zhao; Wei Gu; Zong-Xiu Wu; Jing-Wen Xiang; Qing Yang; Yu-Lin Yang; Lei Tan; Meng-Xia Sun; Wei Cong; Shu Li; Bin-Tong Yang; et al. (Probiotics and Antimicrobial Proteins, 2026)

A comprehensive functional landscape of PRV replication and pathogenesis revealed by genome-wide transposon mutagenesis - Wanwan Yan; Keyue Ruan; Lingchao Chen; Songnan Li; Ting Liu; Wu Tong; Fei Gao; Lingxue Yu; Ning Kong; Guangzhi Tong; Hao Zheng (Veterinary Microbiology, 2026)

PFASs in China’s soils: Temporal declines in legacy compounds mask rising threats from substitutes - Chuan Zheng; Zhenyi Jia; Tong Li; Zhi Wang; Ting Zhu; Xiaoyi Shi (Journal of Environmental Management, 2026)

Inhibitory effect of pulsed electric field pretreatment on acrylamide formation in air-fried French fries and its mechanism - Jian Li; Yue-Wei Huang; Yi-Tong Li; Shi-Yin Luo; Wei-Yan Xiong; Jin-Hua Wang; Jun-Hu Cheng; Ting-Shi He; Xin-An Zeng (Food Research International, 2026)

An AcMYB10-AcF3GT1/GST1 module restricts anthocyanin synthesis in the fruit flesh of kiwifruit - Xiao-tian Li; Zhi-xia Huang; Yu-xiao Zhai; Ya-ting Guo; Yi-tong Liu; Yan Zhang; Zhu Xie; Andrew C. Allan; Xue-ren Yin; Wen-qiu Wang (Plant Cell Reports, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Microfibril orientation and compositional heterogeneity in fiber and vessel cell walls of poplar xylem studied by AFM-IR and SFG spectroscopy - Jongcheol Lee; Juseok Choi; Yen-Ting Lin; Fangxin Qian; Botong Tong; Quanzi Li; Seong H. Kim (Planta, 2026)
Main conclusion This study demonstrates the use of photothermal AFM-IR and vibrational SFG microscopy to investigate nanoscale chemical heterogeneity and mesoscale cellulose microfibril orientation in hybrid poplar xylem, revealing differences in cellulose microfibril (CMF) orientation between fiber and vessel cell walls that are consistent with their mechanical support and hydraulic functions. Abstract Understanding the structural organization of cellulose microfibrils (CMFs) within individual plant cell walls is essential for connecting cell wall architecture to its mechanical and physiological functions. However, due to the complex hierarchical structure and nanoscale heterogeneity of cell walls, it remains technically challenging to resolve detailed compositional and orientational information at subcellular levels of individual cell walls. This study investigates the internal 3D structure, chemical composition, and sublayer organization of fiber and vessel cell walls in the xylem tissue of a two-year-old field-grown hybrid poplar tree ( Populus alba × P. glandulosa ) using photothermal atomic force microscopy coupled with infrared spectroscopy (AFM-IR) and sum frequency generation (SFG) hyperspectral microscopy. AFM-IR provided nanoscale chemical imaging, revealing localized compositional heterogeneity, including variations between adjacent cell walls and transitional layers beyond the traditional S1, S2, and S3 sublayers. SFG microscopy revealed that CMFs in fiber walls are highly aligned along the stem axis, consistent with their role in mechanical support, while vessel cell walls exhibited slightly tilted CMFs, reflecting their function in hydraulic transport. Together, these results offer new insights into cell-type-specific CMF organization and compositional gradients in hybrid poplar xylem. These findings highlight the structural and chemical complexity of secondary cell walls in woody plants and demonstrate the value of AFM-IR and SFG spectroscopy in elucidating plant cell wall architecture. Graphical abstract .

Soil phosphorus dynamics during cropland reforestation - Wenchao Wu; Rongxiao Che; Song Zhang; Yunlong He; Benjamin L. Turner; Dong Liu; Fang Wang; Ting Li; Anquan Xia; Zejin Zhang; Tong Li; Guangbing Xu; et al. (Agriculture, Ecosystems & Environment, 2026)

Method for predicting the microwave heating sensitivity of hard rocks: Application to microwave-mechanical excavation and microwave stress release in tunnels - Shiping Li; Xia-ting Feng; Chengxiang Yang; Feng Lin; Xiangxin Su; Tianyang Tong; Jiuyu Zhang (Journal of Applied Geophysics, 2026)

Nanoliposome strategy for improving bioavailability and anti-acute alcoholic effects of dihydromyricetin through ginsenoside incorporation - Lee-Fong Yau; Meng-Lan Yu; Tian-Tian Tong; Long-Bo Bai; Yu-Hang Zhang; Ya-Ling Yu; Ting Li; Zhi-Hong Jiang (Food Bioscience, 2026)

miR-124 Ameliorates Spatial Memory Deficits in Rats Exposed to Single-Prolonged Stress by Downregulating IQGAP1 to Regulate Actin-Binding Proteins and Apoptosis in Hippocampal Neurons - Qi An; Miao Li; Xin-Yu Ji; Cheng-Hao Piao; Shu-Ting Yang; Lei Tong; Li-Li Ji (Molecular Neurobiology, 2026)

7,8-Dihydroxyflavone attenuates cisplatin-induced cardiomyocyte apoptosis and mitochondrial dysfunction via the p53/Nrf2 pathway - Zhen Tian; Ting-ting Tan; Yu-wei Hu; Jia-tong Yao; Xiao-ting Kang; Jin-yu Zhou; Dong-xu Jia; Qing-liu Li; Ru-jin Liang; Li-mei Zhao; Hua Zhu; Jing Zhao; et al. (Toxicology and Applied Pharmacology, 2025)

Different detoxification strategies of fruit borers adaptation to quercetin - Bing Bai; Huan-Juan Zhao; Bo-Kun Wang; Yu-Ting Li; Ping Gao; Yun-Tong Lv; Xue-Qing Yang (Pesticide Biochemistry and Physiology, 2025)

Synergistic control of antibiotic resistance via natural illite-activated peroxymonosulfate: Efficiency and mechanism - Xiangqin Zhou; Ting Zhou; Jiuqiang Xiong; Wenjun Wang; Yingbin Li; Long Li; Xiang Tang; Zhuotong Zeng; Biao Song; Chengyun Zhou; Jing Tong (Journal of Hazardous Materials, 2025)

SOX11-mediated CBLN2 Upregulation Contributes to Neuropathic Pain through NF-κB-Driven Neuroinflammation in Dorsal Root Ganglia of Mice - Ling-Jie Ma; Tian Wang; Ting Xie; Lin-Peng Zhu; Zuo-Hao Yao; Meng-Na Li; Bao-Tong Yuan; Xiao-Bo Wu; Yong-Jing Gao; Yi-Bin Qin (Neuroscience Bulletin, 2025)
Neuropathic pain, a debilitating condition caused by dysfunction of the somatosensory nervous system, remains difficult to treat due to limited understanding of its molecular mechanisms. Bioinformatics analysis identified cerebellin 2 (CBLN2) as highly enriched in human and murine proprioceptive and nociceptive neurons. We found that CBLN2 expression is persistently upregulated in dorsal root ganglia (DRG) following spinal nerve ligation (SNL) in mice. In addition, transcription factor SOX11 binds to 12 cis -regulatory elements within the Cbln2 promoter to enhance its transcription. SNL also induced SOX11 upregulation, with SOX11 and CBLN2 co-localized in nociceptive neurons. The siRNA-mediated knockdown of Sox11 or Cbln2 attenuated SNL-induced mechanical allodynia and thermal hyperalgesia. High-throughput sequencing of DRG following intrathecal injection of CBLN2 revealed widespread gene expression changes, including upregulation of numerous NF-κB downstream targets. Consistently, CBLN2 activated NF-κB signaling, and inhibition with pyrrolidine dithiocarbamate reduced CBLN2-induced pain hypersensitivity, proinflammatory cytokines and chemokines production, and neuronal hyperexcitability. Together, these findings identified the SOX11/CBLN2/NF-κB axis as a critical mediator of neuropathic pain and a promising target for therapeutic intervention.

A standard for geological evaluation of urban underground space resources in the Beijing plain - Han-han He; Cheng-shan Wang; Jing He; Yuan-xin Zhou; Lei Wang; Stuart Marsh; Chao Li; Tong-ming Fang; Fang-zhen Li; Sheng-li Cao; Jing Liu; Yi-ting Zhao (Bulletin of Engineering Geology and the Environment, 2025)

Comparison of Muscle Texture Characteristics and Nutritional Composition Between Gene-Edited Intermuscular-Bone-Free Crucian Carp and Other Varieties - Huijie Zhou; Zhipeng Sun; Tan Zhang; Tingting Zhang; Ting Yan; Huan Xu; Mingliang Wei; Yashan Yin; Na Li; Youyi Kuang; Guangxiang Tong (Fishes, 2025)
The intermuscular-bone-free crucian carp (Carassius auratus, WUCI), developed through CRISPR/Cas9-mediated bmp6a and bmp6b knockout, offers advantages in consumer acceptance and processing efficiency. However, its effects on muscle texture and nutritional quality have not been fully elucidated. In this study, we compared the F3 generation of WUCI with its sibling wild-type crucian carp (Carassius auratus, WT), Songpu silver crucian carp (Carassius gibelio var. Songpu, SPYJ), and Fangzheng silver crucian carp (Carassius gibelio var. Fangzheng, FZYJ), focusing on muscle texture characteristics and nutritional attributes. WUCI exhibited significantly higher shear force but lower hardness than most comparison groups, with no substantial differences in muscle fiber morphology. Amino acid profiles were similar among all groups. WUCI showed lower crude fat content than WT but higher than FZYJ, and comparable levels of polyunsaturated fatty acids (PUFA), n-3 fatty acids, docosahexaenoic acid (DHA), and eicosapentaenoic acid (EPA) to WT and SPYJ. These findings indicate that the knockout of bmp6a and bmp6b does not alter muscle mass in crucian carp, supporting the potential of WUCI for commercial adoption as a gene-edited consumer-oriented fish product.

Overexpression of G protein-coupled receptors (GPCRs) contributing to lambda-cyhalothrin resistance in Cydia pomonella - Yu-Xi Liu; Chao Hu; Zi-Nan Xia; Yan Wang; Yu-Ting Li; Ping Gao; Yun-Tong Lv; Jia Li; Xue-Qing Yang (Pesticide Biochemistry and Physiology, 2025)

Phytochrome B modulates arsenite stress tolerance and arsenic accumulation in rice (Oryza sativa L.) - Yimei Wang; Shuai Huang; Zongrun Li; Jundan Tong; Yile Sheng; Chun Ye; Weixu Huo; Yafan Zhao; Yanxiu Du; Ting Peng; Jing Zhang (Journal of Hazardous Materials, 2025)

Hydrogel-transformable sucralfate microspheres restored gut epithelial wound and reshaped microbiota in colitis via autophagy - Dingwei Li; Bingjie Tong; Shenyuan Ouyang; Yumo Chen; Jie Wang; Bingyu Ding; Wenzhi Wu; Ting Ouyang; Kaili Mao; Helin Xu (Chemical Engineering Journal, 2025)

Enhancing therapeutic potential of cellular hitchhiking through bioorthogonal chemistry - Jiajia Jia; Maoying Zhang; Aiyang Tong; Ting Fang; Xuerui Ma; Yaying Gao; Jian Zhang; Dongkai Wang; Ji Li (Chemical Engineering Journal, 2025)

Regulating electrostatic microenvironments in robust ultramicroporous metal-organic framework for promoting direct ethylene purification from ternary mixtures - Qiang Zhang; Wenxuan Feng; Yi-Long Li; Lan Lan; Yan-Ting Li; Lu-Lu Wang; Xiaolin Yu; Tong-Liang Hu (Chemical Engineering Journal, 2025)

Thiocyanate transformation mechanisms based on microbial metabolic and treatment technologies for thiocyanate-containing wastewater: A critical review - Yu-Tong Li; Yu Zhang; Wei Wang; Xue-Ting Wang; Xijun Xu; Aijie Wang; Duu-Jong Lee; Nanqi Ren; Chuan Chen (Chemical Engineering Journal, 2025)

Senegenin ameliorates diabetic encephalopathy via promoting mitophagy and repressing NLRP3 inflammasome activation - Xiao-dan Yan; Yu Yang; Wan-ting Zhang; Qing-quan Kong; Xi-tong Zheng; Lin-sen Li; Qing Yu (Psychopharmacology, 2025)

An alternate pathway of antimonite [Sb(III)] resistance in Ensifer adhaerens mediated by ArsZ’ - Ya-nan Wang; Shi-tong Tang; Ya-nan Sun; Xue-ting Li; Jun Zhang (Journal of Hazardous Materials, 2025)

Dual-metal synergy in bismuth-porphyrin nanosheets for enhanced photo-Fenton degradation of ciprofloxacin - Xiao-Huan Liang; Xi Chen; Yuan Chen; Ao-Gang Liu; Ting Zhu; Zi-Tong Chen; Bao Li (Journal of Cleaner Production, 2025)

Switching low-temperature CO2 hydrogenation product selectivity over metal–organic framework derived Co-based catalyst - Yan-Ting Li; Ying-Fei Huo; Yun-Yan Zhong; Lei Zhou; Min Feng; Tong-Liang Hu (Fuel, 2025)

Field Tests Using High-Power Microwaves to Crack Iron Ore of Different Grades - Feng Lin; Xia-Ting Feng; Shi-Ping Li; Tian-Yang Tong; Yun-Tan Ao; Yu-Xi Liu (Rock Mechanics and Rock Engineering, 2025)

Glycosylated protein-related microenvironmental features in breast cancer are associated with patient prognosis - Xiaoxiao Zhong; Jiaxuan Han; Huan Li; Xiangyu Shen; Bowen Yu; Ting Chen; Haobing Li; Jun Li; Jin Pang; Liyuan Qian; Wei Wu; Xiaoliang Tong; et al. (Mammalian Genome, 2025)

Expanding scales: Achieving prediction of van Genuchten model hydraulic parameters in deep profiles by incorporating broad in situ soil information in pedotransfer functions - Yongping Tong; Yunqiang Wang; Jingxiong Zhou; Xiangyu Guo; Ting Wang; Yuting Xu; Hui Sun; Pingping Zhang; Zimin Li; Ronny Lauerwald (Journal of Hydrology, 2025)

Immunomodulatory Effects of Lactiplantibacillus plantarum Strain RW1 During Salmonella Infection in Murine Intestinal Epithelial Cells and Dextran Sulfate Sodium-Induced Murine Colitis - Guangzhi Zhang; Abdul Raheem; Xiaofeng Xu; Xuezheng Fan; Jianwei Zhang; Tong Qin; Li Jia; Min Yue; Weifang Yang; Liang Wang; Mingyan Wang; Yajie Yin; et al. (Probiotics and Antimicrobial Proteins, 2025)

Nutrient supply boosts crop productivity by enhancing soil microbial and faunal interactions - Jianjun DENG; Tong SU; Huijuan ZHANG; Changxu XU; Jia LIU; Peng LI; Ting LIU; Huixin LI; Feng HU; Jiaguo JIAO (Pedosphere, 2025)

Microbial taxonomic diversity and functional genes mirror soil ecosystem multifunctionality in nonferrous metal mining areas - Meng-yao Zheng; Xiao-jun Qi; Zhi-yue Liu; Yi-ting Wang; Yan-bo Ren; Yuan Li; Yue Zhang; Bao-feng Chai; Tong Jia (Journal of Hazardous Materials, 2025)

The substrate configuration influences pollutant removal in constructed wetlands: From the aspects of submerged status of substrate and carbon-felt distribution - Xiang-Zheng Li; Tong Wang; Ting Yang; Xue Li; Lin-Wei Wu; Lin-Lan Zhuang; Jian Zhang (Water Research, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Visible light regulates the activation pathway of periodate on Bi/Mo dual sites for efficient micropollutant degradation: The overlooked roles of metastable complex - Fuyang Liu; Qiqi Dong; Yong Ting; Zhengmao Li; Yanghui Hou; Jialiang Liang; Peng Han; Meiping Tong (Chemical Engineering Journal, 2025)

Nb2CTx modulated glycine film with multi-orientational piezoelectricity and photothermal functions designed for biomedical applications - Weiying Zheng; Tong Li; Lili Qian; Juan Ma; Zhibo Liu; Fei Jin; Zhidong Wei; Ting Wang; Zhang-Qi Feng (Chemical Engineering Journal, 2025)

Protective Effect of Lycium Barbarum Polysaccharides and Sodium Selenite on Cadmium Chloride–Induced Testicular Toxicity in Rats - Xueling Zhang; Yongxin Zhang; Ting Wang; Deng Xiao; Jianding Wang; Chao Ma; Tong Liu; Duoming Zhao; Sheng Li; Junling Wang; Chengyun Li (Biological Trace Element Research, 2025)

Combined use of steam explosion, alkali, and microbial methods improving the yield, structure and properties of soluble dietary fiber from bamboo shoot shells - Yu Wang; Jie Tong; Ting Wang; Ruotong Ma; Mariem Elmalki; Dandan Li; Chuang Li; Zhenglian Xue; Xu Fang; Guangjun Nie (Food Chemistry, 2025)

The Influence of Heterogeneous Processes on the Physicochemical Properties of Atmospheric Aerosols - Maofa Ge; Shengrui Tong; Lin Du; Lingyan Wu; Ting Lei; Kun Li; Minglan Xu; Narcisse T. Tsona; Wenqian Zhang; Hailiang Zhang (Advances in Atmospheric Sciences, 2025)
With the rapid development of the world economy, complex air pollution has increasingly become a serious threat; for example, with haze events occurring frequently in various regions of the globe. Recent evidence has indicated that secondary aerosols play an important role in haze formation, and that heterogeneous processes are among the main forces driving their explosive growth. In this regard, this paper reviews recent advances in the understanding of the impact of heterogeneous processes on haze chemistry, including the impact on NO 2 chemistry, marine aerosols, and the hygroscopicity and optical properties of atmospheric aerosols. It is distinguished from past reviews on this topic by focusing mainly on new insights from the past five years. We summarize the main findings of the impacts of heterogeneous processes on NO 2 chemistry, marine aerosols, and the physicochemical properties of atmospheric aerosols, and propose several future research directions.

Directional anchoring of polymer-lysozyme nanohybrids for adhesive capture and enhanced removal of Alicyclobacillus acidoterrestris in fruit juices - Bingzhi Li; Kun Cheng; Lunjie Huang; Pengyu Chen; Linpin Luo; Liang Zhang; Ting Du; Tong Zhang; Qingqing Li; Yiyue Ma; Bangfeng Fu; Maojun Jin; et al. (Food Chemistry, 2025)

Smartphone-based dual-mode aptasensor with bifunctional metal-organic frameworks as signal probes for ochratoxin A detection - Yu-Long Li; Yan-Yue Chen; Fa-Ting Xie; Qiu-Xia Li; Tong Yang; Yun-Hui Yang; Rong Hu (Food Chemistry, 2025)

Involvement of copper in cell death and cancer - Jiahao Xie; Yue Su; Wenzhong Shang; Yanfang Wu; Junjia He; Ting Li; Yeyu Shen; Youni Zhang; Xiangmin Tong; Qiong Bian (Apoptosis, 2025)

Unlocking dual-mode enzyme activities on bacterial surface: Directional recognition and swift capture of Alicyclobacillus acidoterrestris from fruit juices - Bingzhi Li; Kun Cheng; Pengyu Chen; Linpin Luo; Liang Zhang; Ting Du; Tong Zhang; Qingqing Li; Yiyue Ma; Jing Sun; Maojun Jin; Jianlong Wang; et al. (Food Research International, 2025)

Comprehensive transcriptomic, proteomic, and intestinal microbiota analyses of largemouth bass (Micropterus salmoides) intestines reveal new insights into immune responses to Aeromonas hydrophila infection - Fuyan Chen; Xianhua Ouyang; Zhenping Liao; Ting Huang; Guixiang Tong; Honglian Tan; Mingxu Zhou; Xiaohua Lu; Xinxian Wei; Xueming Yang; Aiying Lei; Jianbin Li (Fish & Shellfish Immunology, 2025)

Anchoring Cu on Zirconium-oxo nodes in a pore-confined metal-organic framework for CO2 hydrogenation to methanol - Chaosheng Bao; Ying-Fei Huo; Yan-Ting Li; Shan-Qing Yang; Wei Li; Tong-Liang Hu (Chemical Engineering Journal, 2025)

PinX1 plays multifaceted roles in human cancers: a review and perspectives - Dian You; Kaiwen Tong; Yuan Li; Ting Zhang; Yongqiang Wu; Ling Wang; Guangming Chen; Xiaoying Zhang (Molecular Biology Reports, 2024)

TFEB/LAMP2 contributes to PM0.2-induced autophagy-lysosome dysfunction and alpha-synuclein dysregulation in astrocytes - Ben Li; Ting Liu; Yongmei Shen; Jiangnan Qin; Xiaohan Chang; Meiqiong Wu; Jianquan Guo; Liangpo Liu; Cailing Wei; Yi Lyu; Fengjie Tian; Jinzhu Yin; et al. (Journal of Environmental Sciences, 2024)

Biodegradation of polybutylene succinate by an extracellular esterase from Pseudomonas mendocina - Ting Hu; Yujun Wang; Li Ma; Zhanyong Wang; Haibin Tong (International Biodeterioration & Biodegradation, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

A novel red fluorescent and dynamic nanocomposite hydrogel based on chitosan and alginate doped with inclusion complex of carbon dots - Yu Lan Tong; Kuan Yang; Wei Wei; Li Ting Gao; Peng Cheng Li; Xin Yi Zhao; Yong Mei Chen; Jianhui Li; Haopeng Li; Hideyuki Miyatake; Yoshihiro Ito (Carbohydrate Polymers, 2024)

Effect of dietary krill oil levels on the regulation of ovary development in Pacific white shrimp (Litopenaeus vannamei) broodstock - Xiaolong Liang; Chang Xu; Ping Wang; Tong Chang; Xianming Xiao; Ting Li; Fenglu Han; Erchao Li (Aquaculture, 2024)

The role of DsbA and PepP genes in the environmental tolerance and virulence factors of Cronobacter sakazakii - Tong Jin; Liuxin Pang; Ting Yue; Lingling Niu; Tingting Li; Yujing Liang; Yunlong Zhang; Chunhong Yan; Baowei Yang; Chunling Zhang; Xiaodong Xia (Food Research International, 2024)

Changes in PI3K/AKT and NRF2/HO-1 signaling expression and intestinal microbiota in bleomycin-induced pulmonary fibrosis - Chenchen Li; Yuxia Cao; Yousheng Peng; Ting Ma; Fanlin Wu; Yongli Hua; Xiuqin Wang; Tong Bai; Yanming Wei; Peng Ji (Food and Chemical Toxicology, 2024)

A Test System for Microwave-Assisted Dual-Mode Mechanical Cutting of Hard Rock Under True Triaxial Compression - Xia-Ting Feng; Xiang-xin Su; Cheng-xiang Yang; Feng Lin; Shi-ping Li; Jiu-yu Zhang; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)
This paper introduces a test system for microwave-assisted dual-mode mechanical cutting of hard rock under true triaxial compression. The test system was developed by Northeastern University, China, to simulate the cutting and breaking of hard rock by a tunnel boring machine (TBM). The test system is mainly composed of a dual-mode mechanical cutting subsystem, a true triaxial loading subsystem and a high-power microwave presplitting subsystem. The system performs dual-mode cutting under true triaxial stress, applies a single sensor to monitor the three-dimensional force of the cutter head, and integrates the reduction in the vibration and resistance to torsion during the cutting process. Mechanical cutting tests of basalt under different amounts of microwave irradiation and true triaxial stress conditions were conducted in Chifeng, Inner Mongolia, China. The results showed that microwave radiation presplitting effectively improved the efficiency of mechanical rock breaking. However, after 180 s of microwave irradiation, true triaxial high stress inhibited the mechanical breaking of basalt in terms of the overall excavation depth. During the tests, each system performed stably. The test results verified the reliability of the test system.

Paraquat disrupts KIF5A-mediated axonal mitochondrial transport in midbrain neurons and its antagonism by melatonin - Huihui Hong; Jingdian Li; Tong Tong; Ting Yang; Hui Wang; Yudong Xu; Xiqin Lin; Jinxian Lin; Sicheng Liu; Kun Luo; Zhengping Yu; Wei Yuan; et al. (Science of The Total Environment, 2024)

Modified halloysite nanotubes as GRAS nanocarrier for intelligent monitoring and food preservation - Qingqing Li; Yuxin Gong; Ting Du; Liang Zhang; Yiyue Ma; Tong Zhang; Zhiyi Wu; Wentao Zhang; Jianlong Wang (Food Chemistry, 2024)

Geochemistry and Zircon U-Pb and Hf Isotopes of Early Devonian Hardawu Granites in the Eastern Segment of the Ultrahigh-Pressure Metamorphic Belt, Northern Qaidam Basin - Hua Li; Ming Wang; Jiqing Li; Haikui Tong; Jiaxiang Dong; Minggang Tian; Xiaolin Chen; Leguang Li; Ting Xie; Xiong Li; Yuying Che (Journal of Earth Science, 2024)

The effect of artificial light at night (ALAN) on the characteristics of diapause of Aedes albopictus - Qing Liu; Heng-Duan Zhang; Dan Xing; Jing-Wen Xie; Yu-Tong Du; Ming Wang; Zi-Ge Yin; Nan Jia; Chun-Xiao Li; Teng Zhao; Yu-Ting Jiang; Yan-De Dong; et al. (Science of The Total Environment, 2024)

Correlation of Immune-Inflammatory Response System (IRS)/Compensatory Immune-Regulatory Reflex System (CIRS) with White Matter Integrity in First-Episode Patients with Schizophrenia - Mengzhuang Gou; Wei Li; Jinghui Tong; Yanfang Zhou; Ting Xie; Ting Yu; Wei Feng; Yanli Li; Song Chen; Baopeng Tian; Shuping Tan; Zhiren Wang; et al. (Molecular Neurobiology, 2024)

Facet-dependent peroxymonosulfate activity and mechanism of CuO for degradation of organic pollutants - Tong Li; Ze-Zhou Ding; Fei Shi; Yi-Ting Ju; Ting-Ting Du; Chang Liu; Xing Zhang (Journal of Environmental Chemical Engineering, 2024)

LRRK2 is involved in heat exposure-induced acute lung injury and alveolar type II epithelial cell dysfunction - Yindan Wang; Wenjun Fan; Guoqing Zhang; Lisha Zhao; Ting Li; Lu Zhang; Tong Hou; Huihua Hong; Zhenqiang You; Qinghua Sun; Ran Li; Cuiqing Liu (Environmental Pollution, 2024)

A novel method to quantify chitosan in aqueous solutions by ultrahigh-performance liquid chromatography–tandem mass spectrometry - Ting Xue; Lei Zhou; Fanjun Wang; Zhuang Tian; Nanxi Li; Tong Ye; Ruolin Hao; Lei Yang; Ruolan Gu; Hui Gan; Zhuona Wu; Xiaoxia Zhu; et al. (Carbohydrate Polymers, 2024)

Combined effects of copper and cadmium exposure on ovarian function and structure in Nile Tilapia (Oreochromis niloticus) - Yijie Wu; Ting Huang; Qiyu Wei; Xin Yan; Liting Chen; Zhirui Ma; Liming Luo; Jinling Cao; Hongxing Chen; Xinxian Wei; Honglian Tan; Fuyan Chen; et al. (Ecotoxicology, 2024)

A hydrogel-based ratiometric fluorescent sensor relying on rhodamine B labelled AIE-featured hyperbranched poly(amido amine) for heparin detection - Cheng Li; Bai-Tong Liu; Yi-Ting Wang; Tian-Jiao Zhang; Xiaochun Zheng; Li Chen; Shaobo Li; Xiaoxian Tian; Dequan Zhang; Yong Wang (Analytica Chimica Acta, 2024)

Overexpression of BRG1 improves early development of porcine somatic cell nuclear transfer embryos - Xuan Ren; Yi Tong; Ting Yang; Shihai Huang; Tairan Xu; Qingsong Xue; Deshun Shi; Xiangping Li (Theriogenology, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Optimization of Microwave Presplitting Iron Ore to Improve Mechanical Mining Efficiency - Feng Lin; Xia-ting Feng; Shi-ping Li; Jiu-yu Zhang; Xiang-xin Su; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)

The Effect of Copper–Cadmium Co-Exposure and Hormone Remediation on the Ovarian Transcriptome of Nile Tilapia (Oreochromis niloticus) - Yijie Wu; Liting Chen; Xin Yan; Jun Xiao; Zhirui Ma; Zhanyang Tang; Zhongbao Guo; Liping Li; Guixiang Tong; Honglian Tan; Fuyan Chen; Xinxian Wei; et al. (Fishes, 2024)
The escalating problem of copper (Cu) and cadmium (Cd) pollution in aquatic environments poses a significant threat to the ovarian tissue and reproductive capacity of fish, hindering the development of the aquaculture industry. However, the combined effects of Cu and Cd on fish gonadal development remain unclear. In this study, the fish species Nile tilapia was stressed with rearing water containing 300 μg/L Cu2+ and 100 μg/L Cd2+ for 30 days, followed by an intraperitoneal injection of luteinizing hormone-releasing hormone (LHRH-α) and human chorionic gonadotropin (HCG) at various concentrations. We investigated the ovarian transcriptome profiles before and after injection. Prior to injection, combined treatment with Cu and Cd resulted in reproductive dysfunction and metal ion imbalance in tilapia. Transcriptomic profiling revealed differential gene annotation concentrated in the MAPK signaling pathway and regulation of GTPase activity. Post-injection, all concentrations of LHRH-α and HCG groups showed an upregulated gonadosomatic index (G.S.I) and higher levels of vitellogenin (VTG), gonadotropin-releasing hormone (GnRH), gonadotropin (GTH), and estrogen (E2) in serum compared to the negative control group. Transcriptomic analysis revealed alterations in various ovarian signaling pathways, preliminarily revealing the in vivo molecular mechanisms and differences in LHRH-α and HCG. The findings from this study could help us better understand how to counteract the effects of combined Cu and Cd exposure on tilapia ovarian development, which has significant implications for the Nile tilapia aquaculture industry.

BRG1 enhances porcine iPSC pluripotency through WNT/β-catenin and autophagy pathways - Xuan Ren; Jianchun Xu; Qingsong Xue; Yi Tong; Tairan Xu; Jinli Wang; Ting Yang; Yuan Chen; Deshun Shi; Xiangping Li (Theriogenology, 2024)

Novel modified semi-carbonized fiber prepared using discarded clothes for derisking Cu(II) and Pb(II) contaminated water - Hong-yan Deng; Yin-fei Wang; Meng-ting Guo; Wen-bin Li; Min Li; Chu-tong Yu (Journal of Environmental Management, 2024)

Nonlinear proinflammatory effect of short-term PM2.5 exposure: A potential role of lipopolysaccharide - Fangxia Shen; Mutong Niu; Haoxuan Chen; Ting Zhang; Jing Li; Haijie Tong; Yan Wu (Journal of Environmental Sciences, 2024)

Arsenic induced neurotoxicity in the brain of ducks: The potential involvement of the gut-brain axis - Shaofeng Wu; Gaolong Zhong; Qian Su; Ting Hu; Gan Rao; Tong Li; Yuhan Wu; Zhiyan Ruan; Hui Zhang; Zhaoxin Tang; Lianmei Hu (Journal of Trace Elements in Medicine and Biology, 2024)

Impact of H2O on CO2 adsorption and co-adsorption: Mechanism and high-performance adsorbents for efficient H2O-CO2 capture - Minghai Shen; Fulin Kong; Wei Guo; Zhongqi Zuo; Ting Gao; Sen Chen; Lige Tong; Peikun Zhang; Li Wang; Paul K. Chu; Yulong Ding (Chemical Engineering Journal, 2024)

Label-free fluorescence detection of human 8-oxoguanine DNA glycosylase activity amplified by target-induced rolling circle amplification - Mengxu Sun; Xiao Chen; Xiang Chen; Qianying Zhou; Ting Huang; Tong Li; Baoping Xie; Chunrong Li; Jin-Xiang Chen; Zong Dai; Jun Chen (Analytica Chimica Acta, 2024)

Cytoprotection of probiotics by nanoencapsulation for advanced functions - Tong Zhang; Congdi Shang; Ting Du; Junchen Zhuo; Chen Wang; Bingzhi Li; Junnan Xu; Mingtao Fan; Jianlong Wang; Wentao Zhang (Trends in Food Science & Technology, 2023)

Integrated multifunctional nanoplatform for fluorescence detection and inactivation of Staphylococcus aureus - Jing-bo Jiao; Qing Kang; Jiang-li Cao; Shuai-qi Zhang; Chen-jing Ma; Tong Lin; Ze-hui Xiao; Chu-min Zhao; Ting Du; Xin-jun Du; Shuo Wang (Food Chemistry, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

DeepAmes: A deep learning-powered Ames test predictive model with potential for regulatory application - Ting Li; Zhichao Liu; Shraddha Thakkar; Ruth Roberts; Weida Tong (Regulatory Toxicology and Pharmacology, 2023)

Salidroside promotes healthy longevity by interfering with HSP90 activity - Jianfei Zhang; Zhiquan Li; Jiangbo Song; Lei Zhou; Xin Chen; Wen Ge; Tianyi Dong; Yuxin Luo; Ting Mao; Zheng Li; Duan Tan; Lene Juel Rasmussen; et al. (GeroScience, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

A new butenolide with antifungal activity from solid co-cultivation of Irpex lacteus and Nigrospora oryzae - Ya-Mei Wu; Xue-Qiong Yang; Jing-Xin Chen; Ting Wang; Tai-Ran Li; Fan-Rong Liao; Run-Tong Liu; Ya-Bin Yang; Zhong-Tao Ding (Natural Product Research, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

CO2 improves the anaerobic biodegradation intensity and selectivity of heterocyclic hydrocarbons in heavy oil - Lu Zhang; Xiangyu Zhou; Chuxiao Hu; Shun Yao; Lei Shi; Tong Niu; Xin Li; Lihua Tong; Jiaqiang Zhang; Ting Ma; Wenjie Xia (Environmental Research, 2023)

The role of reactive astrocytes in neurotoxicity induced by ultrafine particulate matter - Ben Li; Xiaohan Chang; Xiaomin Liang; Ting Liu; Yongmei Shen; Qianwen Zhang; Xiaohui Yang; Yi Lyu; Liangpo Liu; Jianquan Guo; Meiqiong Wu; Yi Gao; et al. (Science of The Total Environment, 2023)

Brittle failure modes of underground powerhouses: an insight based on true triaxial compression tests - Ben-Guo He; Qiang Tong; Xia-Ting Feng; Qiang Jiang; Hui Li; Yonghong Li; Zhiguo Li (Bulletin of Engineering Geology and the Environment, 2023)

Association of urinary metal levels with metabolic syndrome in coal workers - Ben Li; Qianwen Zhang; Xiaohan Chang; Yongmei Shen; Ting Liu; Xiaomin Liang; Qian Gao; Liangpo Liu; Yulan Qiu; Xiaoyan Yan; Jianjun Huang; Tong Wang; et al. (Environmental Science and Pollution Research, 2023)

Efficient acquisition of high-purity cyanidin-3-O-glucoside from mulberry fruits: An integrated process of ATPS whole-cell transformation and semi-preparative HPLC purification - Yi-Tong Li; Ting Huang; Jin-Zheng Wang; Cheng-Hai Yan; Lu-Chan Gong; Fu-An Wu; Jun Wang (Food Chemistry, 2023)

Temporal shell-size variations of bivalves in South China from the Late Permian to the early Middle Triassic - Yunfei Huang; Jinnan Tong; Li Tian; Haijun Song; Daoliang Chu; Xue Miao; Ting Song (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Simultaneous removal of sulfate and nitrate from real high-salt flue gas wastewater concentrate via a waste heat crystallization route - Tong Li; Ting Su; Jiang Wang; Suiyi Zhu; Yuxin Zhang; Zhi Geng; Xianze Wang; Yidi Gao (Journal of Cleaner Production, 2023)

Establishment and comprehensive analysis of a new human cell line (NK-NJ) with NK-cell characteristics established from extranodal natural killer cell lymphoma/leukemia - Jin-Hua Liang; Wei-Ting Wang; Kai-Xin Du; Tong-Yao Xing; Yan Wang; Hui Wang; Lu Liu; Rui Guo; Yang Shao; Junheng Liang; Yue Li; Hao-Rui Shen; et al. (Human Cell, 2022)

The Influence of the Rotary Speed of a Microwave Applicator on Hard-Rock Fracturing Effect - Xia-ting Feng; Shi-ping Li; Cheng-xiang Yang; Feng Lin; Tian-yang Tong; Xiang-xin Su; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2022)

Detection of the role of intestinal flora and tryptophan metabolism involved in antidepressant-like actions of crocetin based on a multi-omics approach - Susu Lin; Qiaoqiao Li; Zijin Xu; Ziwei Chen; Yi Tao; Yingpeng Tong; Ting Wang; Suhong Chen; Ping Wang (Psychopharmacology, 2022)

Antifungal and Antibiofilm In Vitro Activities of Ursolic Acid on Cryptococcus neoformans - Wen-Jing Wang; Chan-Chan Liu; Yan-Tong Li; Miao-Qian Li; Yu-Ting Fu; Xin-Chen Li; Jie-Kang; Wei-Dong Qian (Current Microbiology, 2022)

Genome-wide association study reveals a NAC transcription factor TaNAC074 linked to pre-harvest sprouting tolerance in wheat - Hao Jiang; Yu Fang; Dong Yan; Si-tong Liu; Jun Wei; Fei-long Guo; Xing-ting Wu; Hong Cao; Chang-bin Yin; Fei Lu; Li-feng Gao; Yong-xiu Liu (Theoretical and Applied Genetics, 2022)

Clinical efficacy of melatonin as adjunctive therapy to non-surgical treatment of periodontitis: a systematic review and meta-analysis - Ru-Yue Liu; Lin Li; Zhong-Ti Zhang; Ting Wu; Shuang Lin; Xu-Tong Zhang (Inflammopharmacology, 2022)

Modular-level alterations of single-subject gray matter networks in schizophrenia - Yuxiang Guo; Yunxiao Ma; GongShu Wang; Ting Li; Tong Wang; Dandan Li; Jie Xiang; Tianyi Yan; Bin Wang; Miaomiao Liu (Brain Imaging and Behavior, 2022)

The roles of microRNAs played in lung diseases via regulating cell apoptosis - Qiaoling Huang; Li Chen; Qinqin Bai; Ting Tong; You Zhou; Zhongyu Li; Chunxue Lu; Shenghua Chen; Lili Chen (Molecular and Cellular Biochemistry, 2021)

Three new diterpenoids from Euphorbia peplus - Yan-Ni Chen; Qing-Yun Lu; Dong-Mei Li; Ying-Yao Li; Xue-Xue Pu; Bo-Ting Li; Xiao-Han Tang; Hong-Yu Tang; Shuai Liu; Lei Yang; Yu Zhang; Ying-Tong Di; et al. (Natural Product Research, 2021)

Correction to: Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Phenotypic and genomic adaptations to the extremely high elevation in plateau zokor ( Myospalax baileyi ) - Tao Zhang; Jie Chen; Jia Zhang; Yuan‐Ting Guo; Xin Zhou; Meng‐Wen Li; Zhi‐Zhong Zheng; Tong‐Zuo Zhang; Robert W. Murphy; Eviatar Nevo; Peng Shi (Molecular Ecology, 2021)
The evolutionary outcomes of high elevation adaptation have been extensively described. However, whether widely distributed high elevation endemic animals adopt uniform mechanisms during adaptation to different elevational environments remains unknown, especially with respect to extreme high elevation environments. To explore this, we analysed the phenotypic and genomic data of seven populations of plateau zokor ( Myospalax baileyi ) along elevations ranging from 2,700 to 4,300 m. Based on whole‐genome sequencing data and demographic reconstruction of the evolutionary history, we show that two populations of plateau zokor living at elevations exceeding 3,700 m diverged from other populations nearly 10,000 years ago. Further, phenotypic comparisons reveal stress‐dependent adaptation, as two populations living at elevations exceeding 3,700 m have elevated ratios of heart mass to body mass relative to other populations, and the highest population (4,300 m) displays alterations in erythrocytes. Correspondingly, genomic analysis of selective sweeps indicates that positive selection might contribute to the observed phenotypic alterations in these two extremely high elevation populations, with the adaptive cardiovascular phenotypes of both populations possibly evolving under the functional constrains of their common ancestral population. Taken together, phenotypic and genomic evidence demonstrates that heterogeneous stressors impact adaptations to extreme elevations and reveals stress‐dependent and genetically constrained adaptation to hypoxia, collectively providing new insights into the high elevation adaptation.

Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Recent advances on aptamer-based biosensors for detection of pathogenic bacteria - Danliang Li; Luyao Liu; Qiaoling Huang; Ting Tong; You Zhou; Zhongyu Li; Qinqin Bai; Hao Liang; Lili Chen (World Journal of Microbiology and Biotechnology, 2021)

Chemical composition, antioxidant, antibacterial and cholinesterase inhibitory activities of three Juniperus species - Yujia Zhang; Dong Wu; Shun Kuang; Mingliang Qing; Yue Ma; Tong Yang; Ting Wang; Dengwu Li (Natural Product Research, 2020)

An antiviral drug-resistant mutant of hepatitis B virus with high replication capacity in association with a large in-frame deletion in the preS1 region of viral surface gene - Ting Wang; Yanli Qin; Jing Zhang; Xinyan Li; Shuping Tong; Weifeng Zhao; Jiming Zhang (Virus Genes, 2020)

Liquiritin inhibits proliferation and induces apoptosis in HepG2 hepatocellular carcinoma cells via the ROS-mediated MAPK/AKT/NF-κB signaling pathway - Jia-Ru Wang; Tian-Zhu Li; Cheng Wang; Shu-Mei Li; Ying-Hua Luo; Xian-Ji Piao; Yu-Chao Feng; Yi Zhang; Wan-Ting Xu; Yu Zhang; Tong Zhang; Shi-Nong Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Transcriptome analysis of rice leaves in response to Rhizoctonia solani infection and reveals a novel regulatory mechanism - De Peng Yuan; Xiao Feng Xu; Woo-Jong Hong; Si Ting Wang; Xin Tong Jia; Yang Liu; Shuang Li; Zhi Min Li; Qian Sun; Qiong Mei; Shuai Li; Ki-Hong Jung; et al. (Plant Biotechnology Reports, 2020)

BRAFi induced demethylation of miR-152-5p regulates phenotype switching by targeting TXNIP in cutaneous melanoma - Kezhu Li; Mingrui Tang; Shuang Tong; Chenchao Wang; Qiang Sun; Mengzhu Lv; Xu Sun; Ting Wang; Shifeng Jin (Apoptosis, 2020)

Hostaflavanol A, a new anti-inflammatory and antioxidant activities flavanol from the flowers of Hosta plantaginea - Li Yang; Yi-min Lin; Zhong-wei He; Ting-fang Zhang; Yu Li; Xiao-tong Xie; Yi-feng Wu; Jun-wei He (Medicinal Chemistry Research, 2020)

Environmentally persistent free radicals in PM2.5: a review - Mengxia Xu; Tao Wu; Yu-Ting Tang; Tong Chen; Lavrent Khachatryan; Poornima Ramesh Iyer; Dengting Guo; Anran Chen; Miao Lyu; Jinhu Li; Jiaqi Liu; Dan Li; et al. (Waste Disposal & Sustainable Energy, 2019)

Fusarium oxysporum KB-3 from Bletilla striata: an orchid mycorrhizal fungus - Jianwei Jiang; Ke Zhang; Sheng Cheng; Qianwen Nie; Shen-xian Zhou; Qingqing Chen; Jinglong Zhou; Xiao Zhen; Xue ting Li; Tong wen Zhen; Mingyue Xu; Tom Hsiang; et al. (Mycorrhiza, 2019)

Neuregulin-1β attenuates sepsis-induced diaphragm atrophy by activating the PI3K/Akt signaling pathway - Jin Wu; Hua Liu; Ting Chu; Peng Jiang; Shi-tong Li (Journal of Muscle Research and Cell Motility, 2019)

Reconstruction Model of Ocean Observing Complex Virtual Instrument - Zhijin Qiu; Zhongwen Guo; Yu Wang; Tong Hu; Chao Liu; Ting Li (Journal of Ocean University of China, 2018)

Differential responses of Abies fabri and Rhododendron calophytum at two sites with contrasting pollution deposition and available calcium in southwestern China - Fei-Hua Wu; Juan Chen; Ting-Wu Liu; Zhen-Ji Li; Juan Chen; Lei Chen; Shao-Hua Guan; Tong-Yang Li; Xue-Jun Dong; Janet Patton; Hai-Lei Zheng (Plant Ecology, 2013)

Sulfated modification and cytotoxicity of Portulaca oleracea L. polysaccharides - Tong Chen; Jin Wang; Yuanyuan Li; Jianmin Shen; Ting Zhao; Haixia Zhang (Glycoconjugate Journal, 2010)

A novel endo-glucanase from the thermophilic bacterium Geobacillus sp. 70PC53 with high activity and stability over a broad range of temperatures - I-Son Ng; Chen-Wei Li; Yi-Fang Yeh; Po Ting Chen; Jiun-Ly Chir; Chin-Hua Ma; Su-May Yu; Tuan-hua David Ho; Chii-Gong Tong (Extremophiles, 2009)